2020
DOI: 10.47678/cjhe.vi0.188817
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges to Better Bonds?: Differential On-Campus Participation between International and Domestic Students

Abstract: Helping international students create meaningful on-campus connections is a major part of higher education’s internationalization efforts. By focusing on the efforts made by both international and domestic students to develop a sense of belonging through on-campus organizations like clubs and sports, we have the opportunity to consider their active creation of bridging and bonding capital. Through structured interviews with 150 international Asian and domestic White and Asian students enrolled at one of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Those who attended campus diversity events, orientation, and other events found these activities to be mostly populated with other international students (CBIE, 2015, p. 6;Jiang & Altinyelken, 2022). In their study of a western Canadian university, Malette and Ismailzai (2020) found that Asian international students, who were less likely to take part in sports, fraternities and sororities, and drinking, would participate in ethnicity-focused clubs, which provided them opportunities to form friendships, receive information and emotional support, celebrate holidays and traditions, and feel comfortable and accepted on campus, thus lessening their social isolation and making them feel socially and culturally included (p. 76). The social support internationals students receive from establishing social networks with other students and from participating in campus events contributes to their psychological well-being and positively influences their sociocultural adaptation (Zhou et al, 2008;Zhou & Zhang, 2014).…”
Section: On-campus Events: Social Media Clubs and Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who attended campus diversity events, orientation, and other events found these activities to be mostly populated with other international students (CBIE, 2015, p. 6;Jiang & Altinyelken, 2022). In their study of a western Canadian university, Malette and Ismailzai (2020) found that Asian international students, who were less likely to take part in sports, fraternities and sororities, and drinking, would participate in ethnicity-focused clubs, which provided them opportunities to form friendships, receive information and emotional support, celebrate holidays and traditions, and feel comfortable and accepted on campus, thus lessening their social isolation and making them feel socially and culturally included (p. 76). The social support internationals students receive from establishing social networks with other students and from participating in campus events contributes to their psychological well-being and positively influences their sociocultural adaptation (Zhou et al, 2008;Zhou & Zhang, 2014).…”
Section: On-campus Events: Social Media Clubs and Activitiesmentioning
confidence: 99%
“…Students rely on their new multinational and host-national friends for information and support. Many actively seek to expand different types of friendships by attending orientations, social and cultural events, joining professional clubs, and engaging with others during classes (CBIE, 2015;Couton & Gaudet, 2008;Malette & Ismailzai, 2020;Sherry et al, 2010). Nemera (Pakistani, 18, arrived 2019) found that "there's so many opportunities to get involved" and make friends by joining the Pakistani Student Association (PSA) on campus.…”
Section: Managing Sociocultural Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CJHE shows a marked change around 2014, with a more critical turn emerging in discussions of internationalization. There were still articles examining how to better support international students (e.g., Cui et al, 2017;Giamos et al, 2017;Green et al, 2018;Malette & Ismailzai, 2020;Montsion, 2018;Robertson et al, 2015), but even these took an increasingly critical turn. For example, a number of articles examined the increased vulnerability of international students to personal financial challenges, including food insecurity (Bottorff et al, 2020;Calder et al, 2016;Frank, 2018;Maynard et al, 2018).…”
Section: A Critical Turn: the End Of The International Student Consensus? (2014-2020)mentioning
confidence: 99%
“…Students learn a variety of things outside the classroom through student organizations, including values and camaraderie among the group's members (Borges et al, 2017;Lancaster & Xu, 2017), involvement in student organizations allow for greater interpersonal engagement, networking, and socialization for students (Fazzlurrahman et al, 2018). Malette & Ismailzai (Malette & Ismailzai, 2020). Student organizations have varying effects on academic performance, depending on the type of organization as well as the race and gender of the members (Baker, 2008), as the primary goal of racial/ethnic student organizations is to offer support for students of colour so they can be able to adapt in the campus environment and learn about democracy in the community environment (Bowman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%